2020
DOI: 10.1007/s42761-020-00014-w
|View full text |Cite
|
Sign up to set email alerts
|

Daily Affective Dynamics Predict Depression Symptom Trajectories Among Adults with Major and Minor Depression

Abstract: Affective dynamics have been increasingly recognized as important indicators of emotional health and well-being. Depression has been associated with altered affective dynamics, but little is known about how daily life affective dynamics predict depression's naturalistic course. We investigated positive and negative affective dynamics (e.g., inertia, variability, and instability) among adults with depressive disorders (N = 60) and healthy controls (N = 38) in both cross-sectional and prospective analyses predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 45 publications
3
30
0
2
Order By: Relevance
“…There is some evidence that emotional functioning may predict the course of depression (see Morris et al., 2009, for review). Along these lines, we have also observed in separate studies that patterns of daily life emotional dynamics (Panaite et al., 2020) and autonomic responding (Panaite et al., 2016) predict the naturalistic course of depression in adults. Other work has found that baseline RSA predicts depression symptoms 1 year later among healthy emerging adults (Yaptangco et al., 2015).…”
Section: The Influence Of Development and Early Environmental Factorssupporting
confidence: 59%
“…There is some evidence that emotional functioning may predict the course of depression (see Morris et al., 2009, for review). Along these lines, we have also observed in separate studies that patterns of daily life emotional dynamics (Panaite et al., 2020) and autonomic responding (Panaite et al., 2016) predict the naturalistic course of depression in adults. Other work has found that baseline RSA predicts depression symptoms 1 year later among healthy emerging adults (Yaptangco et al., 2015).…”
Section: The Influence Of Development and Early Environmental Factorssupporting
confidence: 59%
“…In particular, while positive and negative affects are similarly weighted in SWB measures ( 44 ), depression is frequently characterized by more substantial and nuanced changes in negative affect ( 45 , 46 ). Thus, the results presented here suggest that the greater number of social connections in larger cities on the whole may provide a social buffer against negative affect and depression in the most vulnerable people (i.e., those with the smallest social networks).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there are important between-person differences in affect variability. At the extreme, individuals with depression report greater variability in negative affect relative to those without depression (Koval et al, 2013;Lamers et al, 2018;Peeters et al, 2006;Wichers et al, 2010), and greater variability predicts future affect disorder onset and episode recurrence (Houben et al, 2015;Ong & Ram, 2017;Panaite et al, 2020;Wichers et al, 2010).…”
Section: Controllability Of Structural Brain Network and The Waxing And Waning Of Negative Affect In Daily Lifementioning
confidence: 99%